2003
DOI: 10.1002/j.2161-4296.2003.tb00332.x
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Scintillation Effects on GPS in the Equatorial and Auroral Regions

Abstract: Ionospheric scintillation effects on GPS L‐band signals and ultimately on satellite navigation are a growing concern. This concern is due primarily to the losses of lock and cycle slips that intense scintillation may cause in GPS receivers. The most extreme scintillation activity is expected to occur near the equatorial and auroral regions. Less intense scintillation may occur at midlatitudes during geomagnetic storms. In this paper, we summarize recent scintillation activity at Ancon, Peru, and Fairbanks, Ala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
100
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 8 publications
4
100
0
Order By: Relevance
“…This is particularly the case at GPS frequencies, when amplitude scintillation may be completely absent in the presence of phase scintillation (Basu et al, 1998;Doherty et al, 2000;Li et al, 2010). This is sometimes attributed to improper detrending of GPS data as already mentioned at the end of Sect.…”
Section: Discussionmentioning
confidence: 81%
“…This is particularly the case at GPS frequencies, when amplitude scintillation may be completely absent in the presence of phase scintillation (Basu et al, 1998;Doherty et al, 2000;Li et al, 2010). This is sometimes attributed to improper detrending of GPS data as already mentioned at the end of Sect.…”
Section: Discussionmentioning
confidence: 81%
“…Using simultaneous rocket and ionosonde (37.95 • N, 284.53 • E, dip lat. 48.5 • N) measurements, Earle et al (2010) found that the ionosonde detected a mix of range and frequency type spread F during the flight of the rocket, but no significant plasma density structures smaller than a few kilometers were observed in the rocket data. This indicates that the mid-latitude mixed-type spread F only comprises kilometer-scale (without 400 m) irregularities.…”
Section: Discussionmentioning
confidence: 89%
“…The observation indicates that the June solstitial mixed-type spread F is different from that observed during equinoctial months over Sanya. Chakraborty et al (2012) reported that the mid-latitude spread F was mostly of frequency or mixedtype, which could cause VHF scintillation but no GHz scintillation during magnetically disturbed time (Ledvina et al, 2002;Doherty et al, 2003). Using simultaneous rocket and ionosonde (37.95 • N, 284.53 • E, dip lat.…”
Section: Discussionmentioning
confidence: 99%
“…Geomagnetic activity is often used as a convenient proxy to characterize the ionospheric conditions and a clear dependence of temporal and spatial variability of TEC on ionospheric activity has been demonstrated (e.g., Skone et al, 1998). Although scintillation is most intense at low latitudes (Aarons, 1982;Basu et al, 2002) it can be strong in high latitudes during disturbed conditions (Doherty et al, 2004). The high-latitude plasma structure associated with auroral and F-region polar cap patches and sun-aligned arcs is a source of scintillation that has been observed at UHF frequencies (Basu et al, 1987;MacDougall, 1990;Coker et al, 2004).…”
Section: Introductionmentioning
confidence: 99%